Phylogeny and Taxonomy on Cryptic Species of Forked Ferns of Asia - Wei, Zuoying; Xia, Zengqiang; Shu, Jiangping; Shang, Hui; Maxwell, Stephen J.; Chen, Lijun; Zhou, Xile; Xi, Wang; Adjie, Bayu; Yuan, Quan; Cao, Jianguo; Yan, Yuehong (Frontiers in Plant Science, 2022)
Cryptic species comprise two or more taxa that are grounded under a single name because they are more-or-less indistinguishable morphologically. These species are potentially important for detailed assessments of biodiversity, but there now appear to be many more cryptic species than previously estimated. One taxonomic group likely to contain many cryptic species is Dicranopteris, a genus of forked ferns that occurs commonly along roadsides in Asia. The genus has a complex taxonomical history, and D. linearis has been particularly challenging with many intra-specific taxa dubiously erected to accommodate morphological variation that lacks clear discontinuities. To resolve species boundaries within Dicranopteris, we applied a molecular phylogenetic approach as complementary to morphology. Specifically, we used five chloroplast gene regions (rbcL, atpB, rps4, matK, and trnL-trnF) to generate a well-resolved phylogeny based on 37 samples representing 13 taxa of Dicranopteris, spanning the major distributional area in Asia. The results showed that Dicranopteris consists of ten highly supported clades, and D. linearis is polyphyletic, suggesting cryptic diversity within the species. Further through morphological comparison, we certainly erected Dicranopteris austrosinensis Y.H. Yan & Z.Y. Wei sp. nov. and Dicranopteris baliensis Y.H. Yan & Z.Y. Wei sp. nov. as distinct species and proposed five new combinations. We also inferred that the extant diversity of the genus Dicranopteris may result from relatively recent diversification in the Miocene based on divergence time dating. Overall, our study not only provided additional insights on the Gleicheniaceae tree of life, but also served as a case of integrating molecular and morphological approaches to elucidate cryptic diversity in taxonomically difficult groups.